Nghiên cứu ảnh hưởng của các hoạt động quảng cáo trên TikTok đối với ý định mua hàng - Đinh Văn, Hoàng (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study clarifies the influence of social media marketing on Tiktok (SMMA) on purchase intention (PI) in the fashion sector with the mediating role of Brand Awareness (BA) and Brand Image Signal (BI). The study uses Partial Least Squares Structural Equation Model (PLS-SEM) based on 512 survey responses to test the research model. Research results show that social media marketing activities on TikTok have an impact on brand awareness, brand image, and purchase intention. Brand awareness and brand image act as mediators of the relationship between social media marketing activities and purchase intent on the TikTok platform. Thus, the study suggests that small and medium-sized enterprises (SMEs) can take advantage of the TikTok platform to help small and medium-sized businesses achieve their marketing goals and bring business results.
Keywords: Social media marketing activities; Brand image; Brand awareness; SMEs; TikTok; Purchase intention